Believers without Religion: Trends and Paradoxes in Portuguese Society - Teixeira, Alfredo (Journal of religion in Europe, 2019)
By analysing the result of a survey conducted in 2018 in the most populated metropolis in Portugal, this study seeks to make a sociological characterisation of ‘believers without religion’ from a dual perspective: on one hand, their proximity to the non-believers groups regarding religious practices; on the other hand, their adjacency to Portuguese cultural Catholicism with respect to beliefs and attitudes. The growth of this population expresses a paradox: their identity accounts for the subsistence of fragments of a late traditional religiosity, but also points to the emergence of new forms of individual beliefs, strongly marked by the effects of the ‘subjective turn.’ In this context, the lack of institutional regulation does not convey an undetermined universe of believers. Paradoxically, references to cultural Catholicism endure; however, they do so hand in hand with forms of religious abandonment, giving rise to various paths that lead to a growing estrangement from Catholicism.